Piezo1 is required for outflow tract and aortic valve development. (June 2020) - Faucherre, Adèle; Moha ou Maati, Hamid; Nasr, Nathalie; Pinard, Amélie; Theron, Alexis; Odelin, Gaëlle; Desvignes, Jean-Pierre; Salgado, David; Collod-Béroud, Gwenaëlle; Avierinos, Jean-François; Lebon, Guillaume; Zaffran, Stéphane; et al.
Abstract: Aims: During embryogenesis, the onset of circulatory blood flow generates a variety of hemodynamic forces which reciprocally induce changes in cardiovascular development and performance. It has been known for some time that these forces can be detected by as yet unknown mechanosensory systems which in turn promote cardiogenic events such as outflow tract and aortic valve development. PIEZO1 is a mechanosensitive ion channel present in endothelial cells where it serves to detect hemodynamic forces making it an ideal candidate to play a role during cardiac development. We sought to determine whether PIEZO1 is required for outflow tract and aortic valve development. Methods and results: By analysing heart development in zebrafish we have determined that piezo1 is expressed in the developing outflow tract where it serves to detect hemodynamic forces. Consequently, disrupting Piezo1 signalling leads to defective outflow tract and aortic valve development and indicates this gene may be involved in the etiology of congenital heart diseases. Based on these findings, we analysed genomic data generated from patients who suffer from left ventricular outflow tract obstructions (LVOTO) and identified 3 probands who each harboured potentially pathogenic variants in PIEZO1. Subsequent in vitro and in vivo assays indicates that these variants behave as dominant negatives leading to an inhibition of normal PIEZO1 mechanosensory activity. Expressing these dominant negative PIEZO1 variants in zebrafish endothelium leads to defective aortic valve development. Conclusion: These data indicate that the mechanosensitive ion channel piezo1 is required for outflow tract and aortic valve development. Highlights: Hemodynamic forces regulate aortic valve development. Piezo1 a mechanosensitive ion detects these forces. Dominant negative Piezo1 isoforms disrupt aortic valve development. Human patients with mutations in PIEZO1 have LVOTO.